Correlation of Menopausal Status with Body Composition and Abdominal Fat Distribution - Sengar, Mili; Srivastava, Kuldeep; Saxena, Ruchi (National Journal of Community Medicine, 2022)
Background: Body composition parameters changes in women before and after menopause which makes ageing more complex and stressful in women. Objective: to compare the body composition parameters among pre and post menopausal women. Methods: A cross-sectional study, conducted in the population around Rural Health Training Centre (RHTC), Barabanki district between May to December 2016 among women in the age group 25-65 years. Body composition parameters of 348 women (total and visceral fat distribution) by bioelectric impedance method (for Model: OMRON Hbf 375) was noted for all the pre-menopausal and post-menopausal women. The variables included -weight, BMI, body fat percentage (BF %) and visceral fat percentage (VF %), Body Surface Area (BSA), Body volume index (BVI), Body volume (BV) and Lean body weight (LBM). Result: The difference in body composition parameters in the pre and post-menopausal groups is found to be statistically significant in waist circumference, waist-hip ratio, BMI and visceral fat p<0.05. Conclusion: There is increase in body composition parameters during post-menopausal period. A deeper aspect on prevention of obesity after menopause is required to be studied.